AIoT Technologies and Applications for Smart Environments - Alazab, Mamoun (Computing and Networks Series, 2023)
In this edited book, the authors present the challenges, technologies, applications and future trends of the artificial intelligence-enabled internet of things (AIoT) in realizing smart and intelligent environments